Genetic diversity and nitrogen fixation in underutilized tropical legumes - Adegboyega, T.T. (North-West University, 2019)
Legumes in some cases are underutilized and form only a relatively small proportion of human diets. In general they fix atmospheric nitrogen which may provide an economic advantage for smallholder farmers. By appropriate utilization of legumes, food security and soil fertility can be significantly achieved. During the 2016/2017 and 2017/2018 cropping seasons at the International Institute of Tropical Agriculture (IITA) Ibadan, Nigeria, field and laboratory experiments were conducted to determine the genetic diversity and nitrogen fixation of two underutilized tropical legumes, winged bean (Psophocarpus tetragonolobus (L.) DC.) and African yam bean (Sphenostylis stenocarpa (Hoechst ex. A. Rich.) Harms). Twenty-five accessions of each crop were used for these experiments without rhizobia inoculation or N fertilization. In each season, randomized complete block design (RCBD) was used for the filed experiments in three replications. This study confirms characters that can be used to improve African yam bean germplasm include dry pod weight, number of seeds per pod, leaf rachis, terminal petiole length, and seed length. African yam bean fix N and nodulate with indigenous soil bacteria. TSs77 fixed the highest amount of N at 22.47 kg ha-1 followed by TSs30 at 20.91 kg ha-1 and TSs101 at 19.80 kg ha-1. These top three accessions can be identified for breeding programs as superior N-fixing accessions. The protein content of the accessions showed significant differences. For instance, TSs104 had the highest protein content of 25.08%; followed by TSs76 (24.82%), TSs1 (24.52%), TSs4 (24.31%), and TSs67 (24.24%) while the accession with the lowest protein contents in the processed seeds was TSs30 (22.02%). However in the unprocessed seeds, protein content ranged between TSs38 (24.93%) and TSs11 (19.13%). Other proximate analyses evaluated showed differences among the accessions; there were reductions in the unprocessed seeds for phytate and tannin contents. Evidence of the nutritional content of these crops as observed in this study implied that they can be utilized in various dishes for adults and children, to reduce malnutrition in sub-Saharan Africa. No rhizobia were isolated but other isolated root nodule-associated bacteria were analyzed using morphological, biochemical and 16S rRNA. The molecular analysis revealed the presence of Kosakonia oryzae; Enterobacter asburiae; E. cloacae; Ralstonia pickettii; Variovorax sp. and Hydrocarboniphaga effuse. The specific roles of these associated bacteria were not ascertained but previous reports suggest they may assist in plant growth and development. The δ15N signatures of the legume differed among accessions and varied from 2.52 (TSs61) to 0.24 (TSs44) in the shoots and from 2.70 (TSs98) to 0.82 (TSs16) in the roots. Significant differences were recorded among the reference plants used for estimating the percentage N derived from the atmosphere (Ndfa) of African yam bean shoots. TSs76 had the highest Ndfa of 66.73%, 51.83%, and 63.48% followed by TSs4 with 66.18%, 51.03%, and 62.87% while the lowest was TSs1 with 40.07%, 13.22% and 34.21% when Eleusine indica, Zea mays, and Tridax procumbens were used respectively for estimation. The δ13C values of shoots were much greater (i.e., less negative) while the values for the roots also varied considerably. Consequently, the δ13C values of African yam bean shoots ranged from -31.49 (TSs98) to -30.93 (TSs4) and from -31.16 (TSs68) to -30.20 (TSs4) for the roots. The observed variation indicated differences in water-use efficiency among the accessions. The carbon and N ratio (C/N) values were lower than 24 gg-1 and the reference plants had over 24 gg1. These outcomes support the opinion that photosynthetic activities in the underutilized legume were stimulated by N nutrition. TSs44 has a significantly higher number of nodules than other accessions at 169.67 while TSs23 had the lowest number at 58.42. The use of 15N natural abundance method in determining N fixation and water-use efficiency in African yam bean is the first report to the best of my knowledge. The winged bean accessions evaluated possessed the potential to fix nitrogen and also nodulated with indigenous soil bacteria. GCV were high for pod length, dry pod weight, estimated number of seeds per pod, total number of seeds and seed weight. The high GCV suggests that these characters can easily be selected for improvement. In the processed seeds, Tpt17 had the highest protein content of 40.30%, followed by Tpt11 (39.72%), Tpt43 (39.35%), Tpt15-4 (39.21%), and Tpt4 (38.88 %); the lowest was recorded in Tpt48 (34.18%). In the unprocessed seeds, Tpt17 also recorded the highest crude protein content at 31.13%, followed by Tpt4 (31.02%), Tpt15-4 (30.84%), and Tpt42 (30.62%) while the lowest was contained in Tpt125 (28.43%). Other proximate composition analyses suggested that winged bean could serve as a complementary item in human diets and animal feed. In the swollen roots (tubers) and seeds, processing was observed to lower the levels of anti-nutrients. The δ15N values of winged bean showed great differences among the accessions and varied from 3.34 (Tpt18) to 0.86 (Tpt3-B) in the shoots and from 3.07 (Tpt15) to 0.49 (Tpt32) for roots. Among the reference plants used for estimation the percentage Ndfa of winged bean shoots also varied significantly between 66.12% (Tpt3-B) and 24.3% (Tpt18). Differences were seen in the estimation of the roots. The amount of nitrogen fixed differed significantly (p ≤ 0.05) among accessions. The amount fixed (kgN ha-1) in the shoots varied among the accessions with Tpt32 fixing 27.16 kg ha-1, followed by Tpt15-4 at 25.66 kg ha-1 and the accession fixing least was Tpt30 that measured 9.02 kg ha-1 with a considerably lower amount fixed in the root. Variation exists in the carbon and N ratio among the winged bean accessions studied when compared with other parameters analyzed. Overall, the C/N ratio for the shoots ranged from 15.87 (Tpt51) to 11.97 (Tpt32) and from 18.33 (Tpt12) to 17.83 (Tpt53) for the roots. The δ13C values of winged bean shoots ranged from -30.60 (Tpt48) to -29.62 (Tpt19) and from -30.17 (Tpt53) to -19.19 (Tpt6) for the roots. The values obtained showed these accessions were generally stable in their expression of water-use efficiency. Winged bean root nodule-associated bacteria isolated from winged bean roots were Enterobacter asburiae; E. bugandensis; E. cloacae; Enterobacter sp; Enterobacteriaceae bacterium; Pseudomonas cremoricolorata and P. fluorescens. Others are P. montellii; P. putida; Kosakonia oryzae; Ralstonia sp; and an uncultured bacterium clone. Rhizobia recovered from winged bean nodules include Rhizobium mayense, R. multihospitium, R. pusense, and several other rhizobia sp. The rhizobia isolated have been previously confirmed as playing key roles in nodulation and N fixation. This outcome reveals the importance of incorporating legumes in tropical agriculture for crop intensification. Finally, the study provides evidence that African yam bean and winged bean accessions can be improved in a pre-breeding program with respect to the following traits; N-fixing potential, nodulation capacity, proximate and anti-nutritional composition, and diversity in bacteria nodulating the roots.